Effect of grape seed extract (GSE) on functional activity and mineralization of OD-21 and MDPC-23 cell lines - Maria Carolina COELHO; Paula Katherine Vargas SANCHEZ; Roger Rodrigo FERNANDES; Fernanda Panzeri Pires de SOUZA; Selma SIÉSSERE; Karina Fittipaldi BOMBONATO-PRADO (Sociedade Brasileira de Pesquisa Odontológica, 2019)
Abstract Recent studies on functional tissue regeneration have focused on substances that favor cell proliferation and differentiation, including the bioactive phenolic compounds present in grape seed extract (GSE). The aim of this investigation was to evaluate the stimulatory potential of GSE in the functional activity of undifferentiated pulp cells and odontoblast-like cells. OD-21 and MDPC-23 cell lines were cultivated in odontogenic medium until subconfluence, seeded in 24-well culture plates in a concentration of 2x104/well and divided into: 1) OD-21 without GSE; 2) OD-21+10 µg/mL of GSE; 3) MDPC-23 without GSE; 4) MDPC-23+10 µg/mL of GSE. Cell proliferation, in situ detection of alkaline phosphatase (ALP) and total protein content were assessed after 3, 7 and 10 days, and mineralization was evaluated after 14 days. The data were analyzed by ANOVA statistical tests set at a 5% level of significance. Results revealed that cell proliferation increased after 10 days, and protein content, after 7 days of culture in MDPC-23 cells. In situ ALP staining intensity was higher in undifferentiated pulp cells and odontoblast-like cells after 7 and 10 days, respectively. A discrete increase in MDPC-23 mineralization after GSE treatment was observed despite OD-21 cells presenting a decrease in mineralized nodule deposits. Data suggest that GSE favors functional activity of differentiated cells more broadly than undifferentiated cells (OD-21). More studies with different concentrations of GSE must be conducted to confirm its benefits to cells regarding dentin regeneration.